Predicción del crecimiento del ganado en pastoreo con suplementación de melaza y urea - Romero Royo, Francisco (1977)
Tesis (Mag. Sc.) -- CATIE, Turrialba (Costa Rica) -- UCR, San José (Costa Rica), 1977